Fresno County Bar Association Luncheon: Hugh DeWitt speaker re "Star Wars: A Scientist's Perspective" - Watkins, Howard::::::::: (1986)
Robert Wright, Hugh DeWitt and Fresno County Bar Association President Judy Soley at head table; Hilton Ballroom DeWitt -Physicist at Lawrence Livermore National Laboratory